Exploring EFL students’ preferences and practices of study strategies: repeated reading versus testing - Sameer Aljabri (Frontiers in Education)
The aim of this study was to investigate both the hypothetical study strategy (preferences) and actual study (practices) of Saudi EFL undergraduate students regarding rereading versus retrieval practice. A total of 202 EFL students were presented with a scenario where they had studied a textbook chapter once and then asked to choose the learning strategy that best reflected their typical approach during different stages of the learning process: the beginning, middle, and end. Then they read a text and responded to both open-ended and forced report questionnaires to explore their actual study behaviors when studying the text. Results showed a consistent preference for restudying throughout all stages of the learning process (36.5, 39.8, 53.6% respectively). Across the learning processes, retesting strategy has been chosen increasingly as the learning process proceeds (16–18.2 - 28.2%) while rereading is decreasing (35.9–23.8 - 13.3%). In the actual study behaviors, the majority of participants reported tendency to rely excessively on restudying and rereading strategies (55.6 and 24.6% respectively) rather than more effective testing strategies (19.8%). Teachers need to educate students that retrieval practice strategies aid in monitoring their learning progress, enhancing learning, strengthening memory recall, and promoting long-term retention.